Singko-Che - Go, Marie Midel (Animo Repository, 2005)
This is a video documentary about a young Indian's journey to discovering more about 5-6, a practice highly associated with their race here in the Philippines. Along the way, she meets borrowers and moneylenders who share valuable insight into the system of 5-6. A comparison between 5-6 and its closest competitor, the cooperative, is also presented in order to weigh in on the reasons why some people still prefer to borrow from 5-6 moneylenders despite its high interest.